2022
DOI: 10.1161/strokeaha.121.035733
|View full text |Cite
|
Sign up to set email alerts
|

Brain Network Dysfunction in Poststroke Delirium and Spatial Neglect: An fMRI Study

Abstract: Background and Purpose: Delirium, an acute reduction in cognitive functioning, hinders stroke recovery and contributes to cognitive decline. Right-hemisphere stroke is linked with higher delirium incidence, likely, due to the prevalence of spatial neglect (SN), a right-brain disorder of spatial processing. This study tested if symptoms of delirium and SN after right-hemisphere stroke are associated with abnormal function of the right-dominant neural networks specialized for maintaining attention, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Maldonado 42 identified breakdown of brain network connectivity as one of the major underlying causes of delirium. For example, the central nervous system's arousal network, which supports arousal and attention and maintains consciousness, 43,44 likely plays an important role in both disorders 45 . Wakefulness and level of consciousness deficits are well documented in delirium and are also common in spatial neglect 46–48 .…”
Section: Discussionmentioning
confidence: 99%
“…Maldonado 42 identified breakdown of brain network connectivity as one of the major underlying causes of delirium. For example, the central nervous system's arousal network, which supports arousal and attention and maintains consciousness, 43,44 likely plays an important role in both disorders 45 . Wakefulness and level of consciousness deficits are well documented in delirium and are also common in spatial neglect 46–48 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, another fMRI study in patients with right hemisphere stroke found that severity of USN was associated with decreased connectivity of right basal forebrain to brain stem and basal ganglia, as well as increased connectivity within left frontal, temporal, and parietal arousal and attention network regions. 15 Therefore, here we focus on recovery of USN after right hemisphere stroke, consistent with most of the literature on recovery and rehabilitation of USN.…”
Section: Lateralitymentioning
confidence: 96%
“…34 Most studies at that time were relatively small but showed that recovery of USN was associated with increased blood flow in left frontal cortex as well as right parietal cortex 35 or increased glucose metabolism in unaffected areas in both hemispheres. 36 Early activation studies using H 2 15 O positron emission tomography showed that recovery of USN was associated with increased engagement of left frontal eye fields and right superior parietal cortex/precuneus and right parieto-occipital junction, areas previously found to be activated in a spatial exploration task in healthy subjects. 37 Two more recent important studies have used fMRI to evaluate reorganization of neural networks as a mechanism of USN recovery after the first few days following stroke.…”
Section: Subacute and Chronic Recoverymentioning
confidence: 99%
“…A study demonstrated that rs-fMRI could be used to assess the functional reorganization of the injured brain in patients with stroke ( Cui et al, 2022 ). Moreover, Boukrina et al (2022) used rs-fMRI to explore the relationship between arousal network activity and delirium after stroke. rs-fMRI has been widely used in the study of stroke.…”
Section: Introductionmentioning
confidence: 99%